A Igreja - povo de Deus na perspectiva teológica de de Joseph Ratzinger - Silva, Emerson Mozart da (2018)
The XX century, in ecclesiastical scope, is marked by a real ecclesiological renewal. The historical events that marked the first half of the last century of the millennium also influenced the Church in its self-reflection. Ecclesiology was enriched by the enriched by rescue of the theology of the priests of the Church, of the classical liturgy and by the deepening of the studies the sacred scriptures. The emergence of the Nouvelle Théologie provoked theology for the «return of the sources», which was later translated by Pope John XXIII as a necessity of an aggionamento. All this comes to its speak with the celebration of the Second Vatican Council, which is characterized as begin essentially ecclesiastical. For a safe hermeneutic about this great Council, we resort to the contributions of Joseph Ratzinger. Having participated in it as a theologian peritus, he can’t only comprehend within the spirit of the Council, but also contribute with his theological perspective. In the Post-Council period, Joseph Ratzinger gained notoriety with his reflections about the concepts of Church-People of God. Your intuit is demonstrate that going out the «return of the sources» it is possible renew the Church and understand the people starting the Christ body, in a theological perspective markedly sacramental.